2020
DOI: 10.1002/cbf.3493
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin regulates proliferation and cell cycle of cervical cancer by regulating hedgehog signalling pathway

Abstract: Eupatilin (5,7-dihydroxy-3 0 ,4 0 ,6-trimethoxyflavone) is a natural active substance found in génépi group plants, and its pharmacological activities has been proven to be useful in the treatment of various cancers. However, whether eupatilin demonstrates anti-cancer activity in cervical cancer is still under evaluation. To clarify this, cancer cell lines and nude mouse model were used in this study. The results indicated that eupatilin could inhibit the occurrence of cervical cancer both in vivo and in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…In this study, it was confirmed that the mechanism of action of eupatilin previously reported in other cancer cells can be applied to ovarian cancer cells, along with the discovery of newly identified physiological mechanisms and target proteins of eupatilin. Even recently, it has been suggested that eupatilin may have therapeutic effects in cancers derived from female reproductive organs, such as cervical cancer [29]. Furthermore, Jurkat T-cell immune suppression was induced by eupatilin-mediated calcium oscillation and NF-κB inhibition, which is a primary aspect of the pharmacological activity of eupatilin [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was confirmed that the mechanism of action of eupatilin previously reported in other cancer cells can be applied to ovarian cancer cells, along with the discovery of newly identified physiological mechanisms and target proteins of eupatilin. Even recently, it has been suggested that eupatilin may have therapeutic effects in cancers derived from female reproductive organs, such as cervical cancer [29]. Furthermore, Jurkat T-cell immune suppression was induced by eupatilin-mediated calcium oscillation and NF-κB inhibition, which is a primary aspect of the pharmacological activity of eupatilin [30].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that TMP disrupted the Hh signaling pathway to reduce sinusoidal tubule angiogenesis, and to inhibit the angiogenic properties of liver sinusoidal endothelial cells (32). Another study reported that a compound extracted from Artemisia plants reduced the proliferative index of HeLa and Caski CC cells through the Hh signaling pathway, and inhibited tumor growth in tumor-bearing mice (33). Furthermore, sonic Hh gene silencing has been demonstrated to inhibit the epithelial-mesenchymal transition, as well as the proliferation, invasiveness and migration of CC cells by inhibiting the Hh signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of the cell cycle represents an important trait of tumors ( Yu et al, 2020 ). Many anti-cancer drugs inhibit tumor cell proliferation via stalling the cell cycle ( Wu et al, 2020 ). Cos was found to induce G1/S phase arrest in human esophageal carcinoma Eca-109 cells ( Hua et al, 2016b ) and induce G2/M phase arrest in human liver cancer HepG2 cells and breast cancer MDA-MB-231 cells ( Mao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that it suppresses gastric cancer by repressing AKT/GSK3β signaling to inhibit autophagy ( Dai et al, 2021 ). Another reported placenta-specific 8 inhibited oral squamous cell carcinogenesis via blocking AKT/GSK3β signaling pathways ( Wu et al, 2020 ). This study confirmed the inhibitory effects of Cos on the AKT/GSK3β pathway, which was reversed by SC79 (AKT activator) pretreatment.…”
Section: Discussionmentioning
confidence: 99%